Haqaiq al Hayah al Falastiniyyah fi Syi’ir “Yaumiyyat Jarh Falistin” li Mahmoud Darwish - Nushrotun Nida (Journal of Arabic Literature (JaLi), 2021)
Talking about Mahmud Darwis works is as if we were invited to see the real world reality. In this study, the researcher used the object of Mahmud Darwis' poetry entitled "yaumiyyatu Jurhi Falistin" because the poem depicts the real life of the Palestinian people, which is full of sadness and suffering. Therefore, this study aims to determine the real life of the Palestinian people which is described in the poem “yaumiyyatu jurhi falistiin” with the sociology of literature theory by Alan Swingewood and descriptive qualitative methods. The results of the reality of the life of the Palestinian people are described in Mahmud Dawis poetry, namely war, sadness, death and also the patriotism of the Palestinian people in defending their country.